Covid-19 and freedom - Vogt Henri (Sage, 2022)
This article examines the multifaceted nature of freedom in relation to the world's efforts to cope with the Covid-19 pandemic. The aim is to show that in democratic societies, increasing societal regulation to stop the spread of the virus does not necessarily curtail all possible conceptions of freedom. On the contrary, we can even construct new institutional realms or community-strengthening mechanisms through which some forms of freedom can materialise in an unforeseen manner. The heuristic model that informs the analysis is composed of six different embodiments of freedom.